ok, i suppose you want us to solve for the indicated variable.

1. 2x + 3y = 6

=> 2x = 6 - 3y .......................subtracted 3y from both sides

=> x = (6 - 3y)/2 ....................divided by 2 on both sides

=> x = 3 - (3/2)y ....................simplified

2. D = C - s/n

=> D - C = -s/n ......................subtracted C from both sides

=> -n(D - C) = s .....................multiplied both sides by -n

=> s = -n(D - C)

3. A = 1/2 h(B - b)

=> 2A = h(B - b) ...................multiplied both sides by 2

=> 2A/h = B - b ....................divided both sides by h

=> 2A/h - B = -b ...................subtracted B from both sides

=> B - 2A/h = b ....................multiplied both sides by -1

=> b = B - 2A/h ....................rewrite